Complex Positioning System for the Control and Visualization of Photovoltaic Systems - Filip Žemla; Ján Cigánek; Danica Rosinová; Erik Kučera; Oto Haffner (Energies, 2023)
This paper presents a proposal of a complex mechatronic system that enhances the effectivity of obtaining energy from renewable resources. The main focus is on the photovoltaic energy system, which obtains electricity from the conversion of solar radiation through photovoltaic crystalline silicon-based panels. The design of the complex mechatronic system consists of several steps. The structural design of the photovoltaic panel positioning unit in the form of a three-dimensional model is made in the selected modelling programming environment. Subsequently, a propulsion system is proposed for the designed structure, the functionality of which is verified in the programming environment Automated Dynamic Analysis of Mechanical Systems. The control system design using a programmable logical controller is also presented. The corresponding control algorithm is designed in the programming environment Step7 and covers the optimal positioning of photovoltaic panels. The developed application in the WinCC environment provides a visualization of the positioning control process. The conclusion is devoted to the assessment of the obtained results for the proposed complex mechatronic system for photovoltaic panel positioning in comparison with photovoltaic panels in fixed installation. The presented results were obtained by simulations.